2002
DOI: 10.4049/jimmunol.169.12.6760
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of N-Formyl Peptide-Mediated Degranulation by Receptor Phosphorylation

Abstract: One of the major functions of the N-formyl peptide receptor (FPR) is to mediate leukocyte degranulation. Phosphorylation of the C-terminal domain of the FPR is required for receptor internalization and desensitization. Although arrestins mediate phosphorylation-dependent desensitization, internalization, and initiation of novel signaling cascades for a number of G protein-coupled receptors, their roles in FPR regulation and signaling remain unclear. CXCR1-mediated degranulation of RBL-2H3 cells is promoted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…5E. We attribute this variation to reported differences in measurements of TNF-␣ levels possibly due to differences in mast cell cultures, which has also been noted by others (26)(27)(28). These data were similar for huMC (n ϭ 3 donors) (data not shown).…”
Section: Complete Abrogation Of Ros In Wt and 5-lo-deficient Mbmmc Dosupporting
confidence: 77%
“…5E. We attribute this variation to reported differences in measurements of TNF-␣ levels possibly due to differences in mast cell cultures, which has also been noted by others (26)(27)(28). These data were similar for huMC (n ϭ 3 donors) (data not shown).…”
Section: Complete Abrogation Of Ros In Wt and 5-lo-deficient Mbmmc Dosupporting
confidence: 77%
“…ALEXA 546-6-pep (18) and ALEXA 488-GM1 (19) were synthesized as described previously. 6-pep-FITC was from Molecular Probes.…”
Section: Methodsmentioning
confidence: 99%
“…Internalization-deficient mutants of PAFR were used in addition to transient transfections with dominant negative forms for arrestins 2 and 3 and dynamin to demonstrate this phenomenon. Moreover, Vines et al (38) demonstrated that the termination of fMLP-mediated degranulation in transfected RBL-2H3 cells was dependent on receptor phosphorylation and arrestin binding but independent of receptor internalization. We demonstrate here that BLT1 does internalize, and by different strategies we show the importance of BLT1 endocytosis for PLB-BLT cell degranulation.…”
Section: Discussionmentioning
confidence: 99%